Grappling with Realities: Policy and Practice in HIV Social Work. Issue 1 (2nd January 2017) - Hampton, Gary; Buggy, Michael; Graves, Jenni; McCann, Lisa; Irwin, Jude
ABSTRACT: In 2012 the NSW HIV Strategy 2012–2015: A New Era was released, with a goal of eradicating Human Immunodeficiency Virus (HIV) by 2020. This new policy, prioritising biomedical treatment, has raised challenges for social work practitioners working in the HIV field. We undertook a research project exploring the implications of the Strategy on social work clients and practice. A questionnaire was sent to 57 HIV social workers and 32 (56.1%) responses were received. Thematic analysis identified five main themes affecting social workers and their clients. These were a new stigma, treatment benefits, the complexity of people's lives, the psychosocial voice, and ethical and professional tensions. We propose that a more holistic HIV strategy including the psychosocial realities that inform HIV transmission, testing and treatment options, and adherence be adopted.